Advancing Future Amyotrophic Lateral Sclerosis Medicines by Incorporating The Patient Voice Into Patient-Centered Holistic Measurement Strategies for Clinical and Real-World Studies: Results from Targeted Literature Reviews - Diana Rofail; Michael Chladek; Betsy Williams; Nick Patel; William B. Nowell; Stella Karantzoulis; Oren Levy (Neurology and Therapy)
Abstract Introduction This analysis sought to understand the patient experience in amyotrophic lateral sclerosis (ALS) and to assess whether commonly used clinical outcome assessments (COAs) reliably and validly capture that experience. Methods Two targeted literature reviews were conducted to identify and describe key concepts potentially important to patients (signs, symptoms, impacts), and identify commonly used COAs in ALS. Insights gained were used to map target COAs to concepts identified as potentially relevant to patients and their caregivers. COAs of interest were further examined to evaluate evidence of their validity and reliability within ALS. Results Forty-three articles were identified for concept extraction. Signs and symptoms were identified across multiple themes: motor; non-motor; respiratory; cognitive; and behavioral. Patient impacts were identified across multiple themes: physical; functional; emotional; social; and other aspects of well-being. Caregiver impacts were identified across four themes: general; emotional; social; and physical. Of 236 unique COAs identified, 6 were found to provide the greatest coverage of potentially important concepts. Closer examination of these showed some evidence gaps supporting content validity and/or psychometric properties. Conclusions Several concepts related to ALS were identified that are relevant to patients in their daily lives. We identified and reviewed COAs commonly used in assessing these concepts, and found gaps in their content validity and/or psychometric properties. These findings suggest the need for further testing/refinement of existing tools, and the opportunity to use other instruments alongside those most frequently used (e.g., ALSFRS-R) to comprehensively capture the patient experience of ALS in future clinical trial and real-world studies.